ENGLISH VOCABULARY ACQUISITION IN STUDENTS OF INTERMEDIATE LEVEL IN PAKISTAN: CHALLENGES AND STRATEGIES - Aneesa Majeed; Dr. Muhammad Umer Azim; Dr. Muhammad Islam; Mamona Firdous (International Journal of Contemporary Issues in Social Sciences, 2024)
This study investigates the challenges and strategies involved in English vocabulary acquisition among intermediate-level students in Pakistan through a qualitative approach. The primary objective is to identify the barriers students face and the effective strategies they employ to enhance their vocabulary. The research hypothesizes that socio-economic background, teaching methods, and access to resources significantly impact vocabulary acquisition. The population for the study comprises intermediate-level students of govt college of Punjab province. A purposive sampling technique is used to select a sample of 100 students through Yamane formula 1967, ensuring representation from diverse regions and socio-economic backgrounds. The study employs a descriptive research design, focusing on in-depth qualitative data. Data is collected through semi-structured interviews and classroom observations, providing rich, detailed insights into students' experiences and perspectives. The qualitative data is analyzed using SPSS analysis to identify common themes and patterns. The findings aim to provide a comprehensive understanding of the current state of English vocabulary acquisition in Pakistan and suggest practical strategies for educators and policymakers to improve language learning outcomes. The study contributes to the existing literature by highlighting context-specific challenges and proposing tailored interventions to enhance English vocabulary learning among intermediate students in Pakistan.